2017
DOI: 10.1111/jfpe.12614
|View full text |Cite
|
Sign up to set email alerts
|

The convective drying of grape seeds: Effect of shrinkage on heat and mass transfer

Abstract: Detailed knowledge of thermal, hydric and mechanical phenomena within a product during drying helps decrease energy costs by reducing the exposure time and improve product quality by respecting the severe standards requirements. In this context, we simulate the spatiotemporal behavior of a highly deformable product saturated with water during convective drying. The numerical simulation of heat and mass transfer states consists of solving the full conductive solid phase conservation equation, the convecto‐diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Therefore, recent developments in the field of food engineering have led to a renewed interest in the application of drying techniques (of grape residue utilization) to extend the shelf‐life of grape seeds for application in novel food product development. Several attempts have been made on various drying techniques of grape seeds including sun drying (Doymaz, ), supercritical fluid extraction (Prado et al, ), and convective drying (Azzouz, Hermassi, Chouikh, Guizani, & Belghith, ), but the drying methods and conditions have a great effect on physicochemical properties and quality changes of grape seeds. For example, a recent study investigated by Wang et al () reported that drying is directly associated with a change in the physicochemical and biological properties of food materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, recent developments in the field of food engineering have led to a renewed interest in the application of drying techniques (of grape residue utilization) to extend the shelf‐life of grape seeds for application in novel food product development. Several attempts have been made on various drying techniques of grape seeds including sun drying (Doymaz, ), supercritical fluid extraction (Prado et al, ), and convective drying (Azzouz, Hermassi, Chouikh, Guizani, & Belghith, ), but the drying methods and conditions have a great effect on physicochemical properties and quality changes of grape seeds. For example, a recent study investigated by Wang et al () reported that drying is directly associated with a change in the physicochemical and biological properties of food materials.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made on various drying techniques of grape seeds including sun drying (Doymaz, 2012), supercritical fluid extraction (Prado et al, 2012), and convective drying (Azzouz, Hermassi, Chouikh, Guizani, & Belghith, 2017), but the drying methods and conditions have a great effect on physicochemical properties and quality changes of grape seeds. For example, a recent study investigated by Wang et al (2016) reported that drying is directly associated with a change in the physicochemical and biological properties of food materials.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may also be observed in mass diffusion processes in polymers or porous solids, in which diffusion is the chief controller for the movement of the solid phase (Barry & Caunce, 2008). Examples of the mathematical modeling of the drying of food and biological products, which consider shrinkage throughout the process, include the drying of grape seeds (Azzouz, Hermassi, Chouikh, Guizani, & Belghith, 2018), drying of coffee berries (Sampaio, Afonso, & Novo, 2003), drying of cylindrical slices of banana (Saha, Bucknall, Arcot, & Driscoll, 2018), drying of kiwi with hot air and microwaves (Maskan, 2001), shrinkage in biomass pyrolysis (Babu & Chaurasia, 2004; Hagge & Bryden, 2002), drying of longan fruit (Apinyavisit, Nathakaranakule, & Mittal, 2018), and drying of potatoes in a cylindrical shape (Dhalsamant, Tripathy, & Shrivastava, 2017). Although such works agree that the consideration of shrinkage provides more significant parameters and more realistic descriptions of the drying process, none of them propose models with moving boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a mathematical model for the freeze‐drying process is crucial for design engineers to select the appropriate drying conditions that meet the desired operating parameters (Avhad & Marchetti, ). There have been various studies on the modeling of food drying; such as development a model using regression analysis for rehydration kinetics in freeze‐drying of tomatoes (Lopez‐Quiroga, Prosapio, Fryer, Norton, & Bakalis, ), simulation of the spatiotemporal behavior of grapes during convective drying (Azzouz, Hermassi, Chouikh, Guizani, & Belghith, ), prediction of freeze‐dried mushrooms behavior using artificial neural network model (Tarafdar, Shahi, & Singh, ). However, there are not enough studies as yet based on the GEP approach.…”
Section: Introductionmentioning
confidence: 99%